Experimental behaviour of high‐strength concrete deep beams with web openings. Issue 8 (4th August 2011) - Yoo, Tae‐Min; Doh, Jeung‐Hwan; Guan, Hong; Fragomeni, Sam
SUMMARY This paper focuses on an experimental study undertaken on high‐strength concrete (HSC) deep beams with various opening sizes and locations on the web. The test covers a wide scope of variables that have not been investigated in previous research. Apart from highlighting the experimental setup, failure loads and typical crack patterns of the test specimens are also reported. Experimental results are then compared with predictions using currently available design methods. The comparison indicates that the predictions using current design methods can overly underestimate or sometimes overestimate the ultimate strength of these HSC deep beams. Further, the reduction of ultimate strengths due to the existence of web openings is not considered adequately in these design methods. To rectify the shortcomings of current design formulae, a new design equation is proposed and compared with the experimental results and those from previous studies on the related topics. The accuracy and reliability of the proposed new equation is subsequently confirmed. With the outcome of this work, more experimental tests with various opening configurations including shape and location of web openings are recommended for future study. Copyright © 2011 John Wiley & Sons, Ltd.